The effect of early‐life stress on memory systems supporting instrumental behavior. Issue 11 (25th October 2013) - Patterson, Tara K.; Craske, Michelle G.; Knowlton, Barbara J.
ABSTRACT People experiencing early‐life stress (ELS) exhibit increased incidence of behaviors that lead to addiction and obesity as adults. Many of these behaviors may be viewed as resulting from an overreliance on habits as opposed to goal‐directed instrumental behavior. This increased habitization may result from alterations in the interactions between dorsolateral striatum‐dependent and hippocampus‐dependent learning systems. As an initial examination of this idea, we investigated the effect of ELS on instrumental learning and extinction. In Experiment 1, we examined the effect of ELS in two groups of people, one trained on a continuous reinforcement schedule and one trained on a partial reinforcement schedule. We found that people who experienced ELS had a diminished effect of the partial reinforcement schedule on extinction. In Experiment 2, we again manipulated reinforcement schedule and also challenged declarative memory by requiring subjects to perform a concurrent task. We found that the declarative challenge did not affect extinction responding in the non‐ELS group. In a moderate‐ELS group, we observed a diminished sensitivity to the reinforcement schedule during extinction only under divided attention. In the high‐ELS group, we observed a reduced sensitivity to reinforcement schedule even in the absence of the declarative memory challenge, consistent with Experiment 1. Our results suggest that ELS reduces the tendency to use declarative, hippocampus‐dependent memory in instrumental tasks in favor of habits. ELS may affect hippocampal development, thus altering the interaction between memory systems and potentially contributing to poor health outcomes. © 2013 Wiley Periodicals, Inc.